Behaviour of concrete beam reinforced with kenaf fiber mat (KFM) - Wong, Wai Cheng (2017)
There are many researches on external strengthening on the beam using Kenaf Fiber Composite Plate (KFCP) to replace the Carbon Fiber Composite Plate (CFCP) in order to achieve sustainability. This research has been conducted to determine the potential use of kenaf fiber mat (KFM) as reinforcement in beams. The kenaf fibers were treated with 6% of sodium hydroxide (NaOH). The treated kenaf fiber and untreated kenaf fiber samples were prepared for single fiber test. The fiber content considered in this study was 15%, 20%, 25% and 30%. KFM samples for tensile test and flexural test were prepared with respect to the fiber volume ratio. The KFM samples will be undergoing tensile test and flexural test. In this study, a total of 6 beams was examined, which included 2 control beams (without reinforcement), 2 singly reinforced concrete (RC) beams using 2 diameter 10 mm bars and the remaining beams were singly reinforced with KFM. All the beams were tested to failure under three-point loading test. From the tensile test results, KFM samples with 25% of fiber content showed the highest tensile strength at 40.2 N/mm2. KFM with fiber volume ratio 25% exhibited highest flexural strength among the varying fiber volume ratio at 34.1 N/mm2. For the three-point loading tests for beam, the results showed that the KFM beams had increased the ultimate load up to 35% compared to the control beam. Nevertheless, KFM beam only able to reach 31% of the ultimate strength of steel reinforced beam. In terms of crack pattern, similar cracks between the control beam and KFM beams were observed, which failed in bending. The cracking pattern for RC beam can be seen as failure in shear.